Concise account of recent S(N)2 ` grignard coupling reactions in organic synthesis - Kar, Anirban; N. P. Argade (Synthesis-Stuttgart, 2005)
Over the past few decades studies oil controlling the chemo-, regio- and stereoselectivities of allylic Substitution reactions have been well documented in the literature and the S(N)2' Grignard coupling reaction has emerged as a very powerful tool ill selective carbon-carbon bond formation. This review focuses on all the recent synthetic developments in this special class of reactions. 1 Introduction 2 S(N)2' Grignard Coupling Reactions with Allylic Substrates 2.1 Allyl Halides 2.2 Allyl Acetates 2.3 Allyl Carbonates 2.4 Allyl Carbamates 2.5 Allyl Ethers 2.6 Allyl Silyl Ethers 2.7 Allyl Epoxides 2.8 Allyl Aziridines 2.9 Allyl Oxazolidinones 2.10 Allyl Thioethers 2.11 Allyl Benzotriazoles 2.12 Oxabicyclic Alkenes 2.13 Azabicyclic Alkenes 2.14 Oxa-azabicyclic Alkenes 3 S(N)2' Grignard Coupling Reactions with Propargyl Substrates 3.1 Propargyl Acetates 3.2 Propargyl Silyl Ethers 3.3 Propargyl Epoxides 3.4 Propargyl Aziridines 3.5 Propargyl Dithioacetals 3.6 Propargyl Thioethers 4 S(N)2' Grignard Coupling Reactions with Bromoallenes 5 S(N)2' Grignard Coupling Reactions in Natural/Unnatural Product Synthesis 6 Conclusions.
Keywords: allylic substrates; bromoallenes; chiral/achiral S(N)2 ` Grignard coupling reactions; Natural products; propargyl Substrates